Understanding DNA dispersed single-walled carbon nanotube systems - Cathcart, Helen M. (Trinity College (Dublin, Ireland). School of Physics, 2008)
HiPCO Single-walled carbon nanotubes (SWNTs) have been dispersed in water using a variety of different nucleic acids. An extensive study of the factors controlling the quality of the DNA-SWNT dispersions was carried out, allowing one to optimise the sample preparation technique. Numerous different factors, such as improving the sonication process; comparing different DNA types; comparing different DNA:SWNT ratios and the use of centrifugation to remove aggregates and insoluble material were investigated. It was found that the best dispersions were achieved when the samples were sonicated for 2hrs in a small round-bottom flask, suspended centrally in an ice-water sonic bath. It was found that a ratio o f 2:1 (DNAiSWNT) gave the most reproducible samples. In addition, it was found that the samples were improved by centrifuging at 3,300g for 1 hr after sonication to remove any large aggregates that were not broken up during sonication.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin